If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3G + 5 = 11 Reorder the terms: 5 + 3G = 11 Solving 5 + 3G = 11 Solving for variable 'G'. Move all terms containing G to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3G = 11 + -5 Combine like terms: 5 + -5 = 0 0 + 3G = 11 + -5 3G = 11 + -5 Combine like terms: 11 + -5 = 6 3G = 6 Divide each side by '3'. G = 2 Simplifying G = 2
| ln(x+7)=4 | | 5f=25 | | x+2=100 | | 0.04x-0.20(50+x)=-0.04(50) | | 2n+3= | | (z^3)+13=0 | | z^3+13=0 | | 9-3y=0 | | 8x-36=6x-10 | | 3(7+2x)+2(1-x)=19 | | 4(3y-5)+(y+2)= | | x^4-5x^3-3x^2+45x-54=0 | | p-2+5p=2p-6 | | 4r+6= | | 3x-108=108-6x | | 1.5(2x+4*4)=56 | | 4x-2=3x+9x | | 3x*6=50 | | 11x+8=7x+10 | | x(2*3)=12 | | 5(x-40)=30-5x | | x(2*3)= | | 5x-8=83-8x | | 6x+1=2x+33 | | 16x+22=6x+182 | | 12x-2x=4 | | 12x-x=4 | | 12x-1/4= | | 2x+7=5x+2 | | 2x=23x-3 | | 3x+6=64-4x | | 10-(5t+4)=2t-15 |